Upper airways obstruction. Presentation with systemic hypertension. Issue 2 (February 1981) - Serratto, M; Harris, V J; Carr, I
Abstract : Of 14 patients whose final diagnosis was upper airways obstruction associated with heart failure, 3 presented with systemic hypertension (up to 200/100 mmHg). In 2 the hypertension was so severe that at first it had to be considered as a possible cause of the presenting symptoms. The subsequent history indicated that it was an effect of the upper airways obstruction with heart failure.